2022
DOI: 10.15766/mep_2374-8265.11201
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Standardized Patient Caregivers to Practice Difficult Conversations in a Pediatric Dentistry Course

Abstract: Introduction:Standardized patient (SP) methodology has been used in health professional education to help students develop communication, deeper diagnostic reasoning, and critical thinking skills. Few examples demonstrate the use of SPs to practice difficult conversations with pediatric caregivers in the pediatric dentistry literature. The objective of this educational activity was to describe the implementation of three SPs in a pediatric dentistry course for second-year dental students. Methods: We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…32 A study looked at the benefits of setting up a specialist center for patients with SCHN and found that setting up of the center did not change the attitude of students or willingness of graduated students to treat patients with SCD. 33 Other innovations documented included the use of standardized patients 34 and the teaching of disability equality 35 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A study looked at the benefits of setting up a specialist center for patients with SCHN and found that setting up of the center did not change the attitude of students or willingness of graduated students to treat patients with SCD. 33 Other innovations documented included the use of standardized patients 34 and the teaching of disability equality 35 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Recent papers have also found that innovative techniques such as introduction of disability equality training 35 into curricula or the use of standardized patients 34 could have a role to play in teaching SCD. However, these cannot be used as stand‐alone techniques and have been found to be insignificant in the absence of a structured integration into the overall curriculum framework 33 …”
Section: Discussionmentioning
confidence: 99%
“…Many different approaches have been presented about how to improve dental students’ attitudes toward treating underserved populations, 49,50 including frail older adults 51 . These approaches usually include exposure of dental students to underserved populations through community‐based dental education, self‐reflection exercises, case‐based discussions, standardized patients, and scenario simulations, among others 50–53 …”
Section: How To Prepare a Compassionate Dental Workforcementioning
confidence: 99%
“…51 These approaches usually include exposure of dental students to underserved populations through community-based dental education, self-reflection exercises, case-based discussions, standardized patients, and scenario simulations, among others. [50][51][52][53] It is interesting to notice that some studies have reported a decrease in the students' intention to treat frail older adults in their third year of dental school, 50,54 not surprisingly a period when the empathy levels of dental students have been reported at the lowest level. 55 The third year of dental school is usually the time when the students start to have a more intense clinical experience, and therefore it is also the time when students confront their idealistic views about treating patients with the more realistic problems associated with treating frail older adults, such as complex health conditions, long medication lists, behavior issues, communication barriers, time constraints, and others.…”
Section: How To Prepare a Compassionate Dental Workforcementioning
confidence: 99%
“…Simulation labs or standardized patients may also be used to practice these scenarios. Educational sessions with standardized patients have been used to successfully develop communication skills among students in genetic counseling, dentistry, and nursing programs by helping students to hone communication skills, reduce anxiety, and increase confidence when discussing sensitive topics (Kessler et al, 2021 ; Meyer et al, 2022 ; Ok et al, 2020 ). Utility is increased when students are involved in activities with experienced facilitators who can observe, provide support, and offer feedback.…”
Section: Introductionmentioning
confidence: 99%